(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issues of creating a digital learning environment in the modern education system and its impact on the quality and efficiency of education. The possibilities of improving the educational process through the use of digital technologies, information and communication tools and online platforms are highlighted. The positive impact of the digital learning environment on the learning process, independent thinking and creative activity of students is also considered. The article discusses the issues of improving the quality of teaching through the effective use of digital tools in the educational process, and making the educational process interactive and convenient. The research results show that the development of a digital learning environment is an important factor in increasing the efficiency of the education system.